STRATEGI PEMENUHAN KEBUTUHAN EKONOMI JANDA CERAI MATI - Kholid Mawardi; Siti Ma'sumah; Faradiena Zulizar (IAIN Purwokerto, 2017)
Abstract: Islam is very protective of women. This can be seen from the verses of the Qur'an and Hadith about the responsibility of a father to the daughter and the husband's responsibility to his wife. From the results of the study, it can be concluded that all informants do not have a permanent job. They just have coarse work and more important is getting money. All informants have dependence on the help of others, whether it's a big kid, neighbors, relatives, friends and even boss. All informants felt that the cost of electricity and gas facilities was high. The costs of other facilities such as vehicles, proper houses and others for them are very unlikely to be fulfilled as they are very big. Social costs such as attending celebrations, visiting sick people and others also they feel very heavy, but they still do it, because they live in the community to get along with neighbors. In fact, all informants prefer social costs rather than the cost of personal needs such as meals, clothing and others. All informants have experienced life deficiency. All informants are very simple in life. Almost all informants applied a system of hole digging holes to fulfill their needs. The divorced widows who become informants rely on neighbors, relatives, children who are independent and the boss to lend them money. Keywords: Hard work, Dependency, facility costs, digging hole, closing hole.